Basic training in "participatory practice" to foster municipal health equity in Germany. (20th October 2021) - Bär, G; Kasberg, A; Markert, C; Speltz, Z; Griebel, F; Schaefer, I
Abstract:  : Participation is a key strategy in municipal health promotion and health equity. Short-term trainings for professionals and activists are missing in Germany. Therefore, a curriculum was developed together with experienced health promotion professionals and Public Health scientists. The course aims at the development of competencies as well as at practical training. Essentials to the curriculum are main principles of participatory approaches, academic and practice-based knowledge on methods of community-based research. The evaluation asked: -Which amount of in-class time and field training is needed? How can elements of 'participatory training' be implemented? What support is given to transfer the course contents into practice? Two pilot series with in sum 25 participants were conducted. This led after evaluation to a five days' curriculum of training, divided on two workshops plus a midterm online-meeting. Training material on participatory approaches and step-by-step-descriptions on six methods were developed. An own practice project is embedded in the program. Experienced trainers introduced the methods and led seminar sessions. Elements of 'participatory training' were implemented as follows: in the application as teams of two, in telling project stories to introduce new methods, supporting peer-to-peer-reflection and learning from each other. Support was provided through a virtual course platform for the group exchange and individual consulting. After evaluation informal meet-ups and monthly tasks were added to the course. In the pre-pandemic series all teams designed and started own projects. There is a high need in the field of municipal health promotion to implement community-based participation in Germany. Thus, classes were quickly booked out and evaluation showed a high motivation in working more participatory after the course. The curriculum is going to be published open access. Several health promotion associations are interested in offering the program. Key messages: There is a high need in the field of municipal health promotion to implement community-based participation in Germany. The curriculum is going to be published open access. Several health promotion associations are interested in offering the program.